On expressive and aesthetic use of terminology: an attempt of communicative analysis (with russian and croatian linguistic terms as examples) - Albrekht Fedor (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
This article analyses several Russian and Croatian linguistic terms and aims to demonstrate that linguists tend to equate characteristic features of communicative situations with features of linguistic units occurring in these situations. The terms coined to be exact designations of a certain scientifi c notion and used in the academic style are perceived by many scholars as signs devoid of any emotion and expressiveness. Clearly, the use of terms does not imply any expressiveness if they are employed for the purpose they have been created for, namely for the sake of alloting the exact name to a newly-discovered phenomenon and incorporating the given name into the existing terminological framework. However, the coinage of terms sometimes ceases to be a vital need and transforms into designating something new for the sake of it, which conceals a totally diff erent aim. This aim might be, e.g., designating oneself as different from “laymen”, and to this end terms of foreign origin are readily at hand (the tendency to alienate terminology from everyday language). This aim might also be the demonstration of the fact that a certain language can well serve as a language of science and elite culture making use of its own resources of word formation and semantics (the tendency to create new words despite the established tradition and in contrast to the opinion of another nation about this language). Thus, if creating terms transforms from a vital need into the process of designating for the sake of it, the main communicative aim of employing terms also shifts from its academic function to serving the goal of the writer/speaker to alienate him- or herself from anybody else (laymen, non-professionals, other nations etc.). And it is in this case that the use of terminology becomes expressive. Consequently, the expressiveness of the term is not determined by the properties of the term as a linguistic unit because these properties are secondary with regard to the initial intention of the speaker/writer.